Photodynamic therapy with talaporfin sodium for endoscopically unresectable gastric cancer using a novel simultaneous light‐emitting method - Tomoyuki Hayashi; Kotaro Hayashi; Takeshi Terashima; Masaki Nishitani; Noriaki Orita; Masaki Miyazawa; Akihiro Seki; Hidetoshi Nakagawa; Kouki Nio; Noriho Iida; Shinya Yamada; Hajime Takatori; et al. (DEN Open)
Abstract We describe a case of gastric cancer treated by photodynamic therapy (PDT) with talaporfin sodium using a novel simultaneous light‐emitting method. An 82‐year‐old man was diagnosed with gastric cancer near the cardia with suspected deep submucosal invasion. Surgical resection was deemed high‐risk owing to an underlying pulmonary disease. After ruling out endoscopic procedures due to intense fibrosis resulting from the scarring, PDT with talaporfin sodium was chosen. PDT was successfully conducted using an endoscope with simultaneous light emission. The patient experienced a complete response to the treatment and showed no signs of recurrence during follow‐up. This case highlights the potential of PDT with talaporfin sodium as a viable alternative for challenging cases, particularly in patients unsuitable for surgery and endoscopic resection. Furthermore, the novel simultaneous light‐emitting method may improve the efficiency of the procedure. This case demonstrates the potential of PDT in gastric cancer treatment, especially for high‐risk patients.